2011
DOI: 10.1038/nphys1980
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved imaging of purely valence-electron dynamics during a chemical reaction

Abstract: Chemical reactions are manifestations of the dynamics of molecular valence electrons and their couplings to atomic motions. Emerging methods in attosecond science can probe purely electronic dynamics in atomic and molecular systems [1][2][3][4][5][6] . By contrast, time-resolved structural-dynamics methods such as electron 7-10 or X-ray diffraction 11 and X-ray absorption 12 yield complementary information about the atomic motions. Time-resolved methods that are directly sensitive to both valence-electron dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
189
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(193 citation statements)
references
References 28 publications
4
189
0
Order By: Relevance
“…It has been shown that (at least) partial alignment of molecular axes improves the sensitivity of the PAD to electronic character; this alignment can be achieved through photoexcitation, through strong-field alignment methods, or through coincidence imaging. [6][7][8][9][10][11] In the atomic case, alignment of orbital angular momentum serves the same purpose as alignment of molecular axes, and a number of laser-based studies have shown that achieving this through photoexcitation prior to photoionization can lead to a PAD with exquisite sensitivity to the angular momentum composition of the intermediate state. [12][13][14] However, although systematic studies have been performed in which different intermediate electronic states are prepared, generally only a single ionic electronic state has been accessible in each case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that (at least) partial alignment of molecular axes improves the sensitivity of the PAD to electronic character; this alignment can be achieved through photoexcitation, through strong-field alignment methods, or through coincidence imaging. [6][7][8][9][10][11] In the atomic case, alignment of orbital angular momentum serves the same purpose as alignment of molecular axes, and a number of laser-based studies have shown that achieving this through photoexcitation prior to photoionization can lead to a PAD with exquisite sensitivity to the angular momentum composition of the intermediate state. [12][13][14] However, although systematic studies have been performed in which different intermediate electronic states are prepared, generally only a single ionic electronic state has been accessible in each case.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This idea has been put to use in studies of photodetachment from anions, 4,5 and elegantly exploited in femtosecond time-resolved photoelectron imaging studies of non-adiabatic dynamics in neutral molecules. [6][7][8][9] Given this interest, there is a need for systematic studies of the variation of PADs with the electronic state of the neutral and the ion. It has been shown that (at least) partial alignment of molecular axes improves the sensitivity of the PAD to electronic character; this alignment can be achieved through photoexcitation, through strong-field alignment methods, or through coincidence imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, real-time imaging of electron dynamics is one of the most important goals for modern ultrafast science [1][2][3][4][5][6][7][8][9]. In this article, we investigate the opportunities for applying ultrashort extreme ultraviolet (XUV) probe pulses inducing single-photon ionization for imaging coherent electron dynamics in molecules by means of timeand angle-resolved photoelectron spectroscopy (TRARPES), i.e., time-and energy-resolved molecular-frame photoelectron angular distributions.…”
Section: Introductionmentioning
confidence: 99%
“…We mention here high-order harmonic-generation (HHG) spectroscopy [8][9][10][11][12] and laser-induced electron diffraction (LIED) [9,[13][14][15][16][17][18]. Time-resolved photoelectron spectroscopy (TRPES) and time-resolved molecular-frame photoelectron angular distribution (TRMFPAD) measurements proposed recently [19,20] are capable of imaging valence-electron dynamics and atom motion during a chemical reaction. In this approach, the temporal resolution is limited to about hundreds of femtoseconds, owing mostly to the vacuum ultraviolet (VUV) laser pulse duration used in the experiments.…”
Section: Introductionmentioning
confidence: 99%